Trusting Doctors : The Decline of Moral Authority in American Medicine - Imber, Jonathan B., 1952- (Book collections on Project MUSE., 2008)
Discusses the emphasis that Protestant clergymen placed on the physician's vocation; the focus that Catholic moralists put on specific dilemmas faced in daily medical practice; and the loss of unchallenged authority experienced by doctors after World War II, when practitioners became valued for their technical competence rather than their personal integrity. Imber shows how the clergy gradually lost their impact in defining the physician's moral character, and how vocal critics of medicine contributed to a decline in patient confidence. The author argues that as modern medicine becomes defined by specialization, rapid medical advance, profit-driven industry, and ever more anxious patients, the future for a renewed trust in doctors will be confronted by even greater challenges.